A case of pulmonary ALK-positive histiocytosis combined with Birt-Hogg-Dubé syndrome carrying an EML4::ALK gene fusion: a case report and literature review - Yang, Shuzhe; Bai, Zhongyuan; Zhao, Qi; Wang, Yajing; Xi, Yanfeng (Frontiers in Immunology, 2025)
In this article, we report the first case of a 61-year-old woman who was diagnosed with both nodules and cystic lesions in her lungs. The lung nodules were diagnosed as ALK-positive histiocytosis (APH) carrying an EML4::ALK gene fusion, which microscopically displayed a mixed morphology of foamy cells, spindle cells, and Touton’s giant cells. Immunohistochemistry showed expression of CD163, CD68, and ALK, while fluorescence in situ hybridization (FISH) with second-generation sequencing (NGS) showed the ALK gene fusion with the FLCN gene variant. The patient also had bilateral multiple cystic lesions in the lungs, which were morphologically consistent with pulmonary bullae. The FLCN gene variant, in combination with the results of NGS, led to the diagnosis of Birt-Hogg-Dubé syndrome (BHD). APH and BHD are very rare, and it is easy to misdiagnose or miss the diagnosis altogether if one is not familiar with the associated histology and immunohistochemistry. It is essential for pathologists to recognize the presence of these two diseases and understand the associated histomorphologic, immunohistochemical, and cytogenetic features to enable an accurate diagnosis and differential diagnosis.